A Patchworking Process: Coming Together under Pandemic Conditions for Collaborative, Caring Scholarship - Carlson, Rebecca; Golovátina-Mora, Polina; Peterken, Corinna; Snepvangers, Kim; Soronen, Anne; Talvitie-Lamberg, Karoliina (Imaginations, 2021)
In the context of the COVID-19 outbreak, the authors in this special issue came together within the Massive Microscopic Sensemaking (MMS) writing project in the spring of 2020. Collectively grappling with the impact of the extended pandemic, each paper in this issue touches on experiences of social isolation, making do, and a technological reaching out under conditions of a public health crisis. This introduction describes the issue’s ‘patchwork’ development which reflects an attempt to break from traditions of academic scholarship that often fail to recognize the value of emergent, and therefore uncertain, cross-disciplinary and collective work.